High-touch, low-tech: Investigating the value of an in-person library orientation game. Issue 1 (2nd January 2018) - Vrbancic, Emilie K.; Byerley, Suzanne L.
ABSTRACT: Since 2011, the Kraemer Family Library at the University of Colorado Colorado Springs (UCCS) has offered Scrabble Scramble, an in-person, student-centered library orientation game, to incoming first-year students. This article describes our journey of developing, assessing, and refining Scrabble Scramble, which focuses on introducing first-year students to the basic services and resources of an academic library. Through analysis of student and library staff feedback survey results, this article reflects on the value of offering a student-centered, impactful, and personal orientation in an environment of rising student enrollment, steady staff numbers, and a trend to move orientation activities online.